Some fixed point theorems for Kannan mapping in the modular spaces - Ghoncheh, S. J. Hosseini (Ciência e Natura, 2015)
In this article, a new version of Kannan mapping theorem in modular space is presented. The main result of this paper is the existence of fixed point of Kannan mapping in complete modular spaces that have Fatou property.